3D Interactive Virtual Reality Media to Improve Learning Outcomes in Thematic Subjects - Cepi Riyana; Budi Setiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
At the elementary level of school, learning activities are encouraged to prioritise student participation and interaction in the learning process. This is done in order to maximise the overall educational experience. Utilising different kinds of educational media that are based on technology is one of them. It is with media that is based on virtual reality (VR), which gives users the ability to interact with goods in a virtual setting that not only appears real but also has the sensation of being real. This study aims to develop 3D Virtual Reality Interactive Media to improve student learning outcomes in elementary schools. A quasi-experimental approach was utilised for the methodology of this research, and pre- and post-test control groups were included. The learning achievement test is the tool that is being utilised in this research. Students in fourth grade from elementary schools participated in the research project. The following are some of the findings that emerged from this research: (1) the development of a model for 3D virtual interactive multimedia; (2) the implementation of learning through 3D virtual reality interactive media utilising a systems perspective; (3) Varieties of learning assessment (assessment) that make use of authentic assessment; (4) Data demonstrating a good response from students towards the implementation of 3D virtual reality interactive media. It has been demonstrated that the implementation of interactive media in the form of 3D virtual reality has been successful in enhancing the learning outcomes of students in Thematic Subjects, particularly Science in Elementary Schools.